To solve the quadratic equation \( x^2 - 22x + 1 = 15 \) by completing the square, follow these steps:
-
Start by moving the constant term to the right side of the equation:
\[ x^2 - 22x + 1 - 15 = 0 \]
Simplifying this gives:
\[ x^2 - 22x - 14 = 0 \]
-
Next, complete the square. Take half of the coefficient of \(x\) (which is \(-22\)), square it, and add it inside the equation:
Half of \(-22\) is \(-11\), and squaring it gives \(121\). So we adjust the equation as follows:
\[ x^2 - 22x + 121 - 121 - 14 = 0 \]
This simplifies to:
\[ (x - 11)^2 - 135 = 0 \]
-
Rearranging gives us:
\[ (x - 11)^2 = 135 \]
-
Now, take the square root of both sides:
\[ x - 11 = \pm \sqrt{135} \]
-
Finally, solve for \(x\):
\[ x = 11 \pm \sqrt{135} \]
Since \(\sqrt{135} = 3\sqrt{15}\), we can rewrite it as:
\[ x = 11 \pm 3\sqrt{15} \]
So, the correct responses from the options given would correspond to:
\[ x = 11 + 3\sqrt{15}, \quad 11 - 3\sqrt{15} \]
Thus, the correct answer is:
x = 11 + 3√15 , 11 - 3√15.